The impact of COVID-19 pandemic on financing the purchase of residential real estate through a mortgage in Poland - Sadowa, Agnieszka (University of Wroclaw. Faculty of Law, Administration & Economics, 2021)
The study analyses the changes in financing the purchase of residential real estate based on a mortgage in Poland, caused by the outbreak of the COVID-19 pandemic in its initial stage, that is, the period from March to September 2020. There search problem is the impact of the pandemic on the process of granting and repaying loans for housing purposes. Banking institutions tightened the terms of granting financing. People who received financing earlier may, however, benefit from assistance in paying off the debt. The research hypothesis assumes the negative consequences of the COVID-19 pandemic for the consumers of the housing loanmarket in the analysed period. The research methods used are the analysis of statistical data and facts. The author looks at the situation on the real estate market and the situation on the housing loan market in 2020. The study then highlights the actions of lending banks and the actions of buyers in the first pandemic months.
Keywords: financing; real estate; residential real estate; Poland; mortgage; COVID-19 pandemic; creditworthiness